Kombinasi Yoga dan Herbal dalam Pengobatan Beserta Efektivitasnya - I Gusti Agung Ayu Kartika; Made Krisna Adi Jaya (UHN IGB Sugriwa Denpasar, 2022)
Yoga is often combined with other types of therapy to maximize the patient's treatment. Combinations of yoga and herbs is one of the possible combinations. This study aims to summarize and review research results related to the combination of yoga and herbs. Research articles are collected from various online databases such as Google Scholar, Google, Medline, Pubmed, and Science Direct. Inclusion and exclusion criteria were applied to obtain clinical research articles that were original, relevant to the topic of interest, published in the last 10 years, full text accessible, also methods and results were described well and valid. In total there are only 5 articles that qualify for discussion. The research was conducted in Indonesia and India. The herbs were used in inhalation and oral forms. Indications for the use of a combination of yoga and herbs are reducing dismenorrhea pain, cronic joint pain, helping treat type 2 diabetes mellitus, hypertension, and improving sleep quality. The combination of yoga and herbs is still not widely applied and studied. It opens up great opportunities for further research.